Akselerasi Entrepreneurial Spirit: Implementasi Pembelajaran Berbasis Proyek Mandiri pada Mahasiswa Akuntansi - Eka Farida; Afi Rachmat Slamet (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
The current paradigm shift in higher education mandates that accounting students look beyond technical competencies to cultivate psychological resilience as job creators. This qualitative study, utilizing a case study approach within the Accounting Department at Universitas Islam Malang, aims to explore the efficacy of implementing project-based learning to accelerate students' entrepreneurial spirit. Research data were compiled from business design drafts, independent retail project reports, and the dynamics of collaborative group work. The findings indicate that the syntax of project-based learning successfully internalizes a strong work ethic, sharpens leadership qualities, and heightens awareness of business risk management. Operational hurdles encountered by students served as a positive catalyst to stimulate product creativity and collective problem-solving capabilities, with project success heavily influenced by the adaptation of learning styles in managing conflicts. This study concludes that independent project methods effectively mitigate the job-seeker mentality toward becoming job creators. Its implications underscore the urgency of reconstructing the accounting curriculum through the integration of empirical retail practices to establish a sustainable entrepreneurial ecosystem in higher education.